PENGARUH PERMAINAN EDUKATIF GO FISH TERHADAP HASIL BELAJAR KOGNITIF MENGUBAH PECAHAN KE PERSEN DAN DESIMAL KELAS V SEKOLAH DASAR - Amalia, Zahratul; Zainil, Melva; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
This study aims to know the effect of go fish educative game to the cognitive learning outcomes of change fractions to percent and decimal forms. This research was an experimental research design with quasi exsperimental with nonequivalent  pretest-posttest control group design. The sample in this research used two classes, there were an experiment class and a control class. The calculation result of research data used was obtained t-test t0(2,817) > ttable (1,684) at α level of 0.05. With it can be concluded that there was the effect of go fish educative game to the cognitive learning outcomes of change fractions to percent and decimal forms in V grade of elementary school.  Key Word : Game, Go Fish, Fractional Learning Outcomes